IMMU-06. TARGETING IDH1 MUTANT GRADE II RECURRENT GLIOMAS USING A PEPTIDE VACCINATION STRATEGY. (21st September 2021) - Mohan, Aditya; Peters, Katherine; Hotchkiss, Kelly; Batich, Kristen; Congdon, Kendra; Vlahovic, Gordana; Archer, Gary; Norberg, Pamela; Xie, Weihua; Herndon, James; Jaggers, Denise; Landi, Daniel; et al.
Abstract: INTRODUCTION: While primary GBM is largely heterogeneous and devoid of homogeneously expressed neoantigens, mutant IDH1 (R132H) is a uniformly expressed hallmark in >70% of low grade gliomas. As such, IDH1 mutations represent a potentially valuable vaccination target. METHODS: Here, we report an update on the immunogenicity results of the mutant IDH1 peptide vaccine alone and in combination with temozolomide (TMZ). In the phase I RESIST clinical trial (NCT02193347), patients with recurrent and resectable IDH1 R132H mutant grade 2 glioma received peptide vaccinations composed of 500 µg of mutant IDH1 peptide and 150 µg of GM-CSF mixed 1:1 with Montanide adjuvant prior to surgical resection. Vaccines 1, 2, and 3 were given 15 (+/-) 3 days apart. 7-12 days after vaccine 3, patients underwent standard of care tumor (SOC) resection. After resection, patients with grade 2 gliomas were given up to 15 doses of peptide vaccine in combination with TMZ regimens while patients with transformed grade 3 gliomas were given up to 15 doses of peptide vaccine in combination with SOC radiation therapy + TMZ regimens. T cell responses against the mutant peptide were measured after vaccine 3 using IFN-γ ELISPOT and intracellular flow cytometry for IL-2, TNFα, and IFNγ. RESULTS: 3/20 patients were taken off the study before completion of study related activities. 1/20 patients progressed before completion of all vaccines. Out of 134 total doses of vaccine delivered, only one dose generated a grade 2 or higher injection site reaction according to the CTCAE guidelines. Vaccination with the mutant peptide led to an overall increase in IFN-γ+ spot-forming splenocytes specific to the mutant peptide (p=0.0408). CONCLUSION: Administering the mutant IDH1 peptide vaccine in patients with recurrent IDH-mutant gliomas was able to induce anti-IDH1 R132H immune responses in this initial phase I study.